Evaluation of 1D and 3D CFD Simulation Methods for Exhaust Backpressure - Rudravajhala, Mukund (My University, 2018)
An internal combustion engine generates exhaust gases that need to be transported away from the engine and also the passenger cabin. This is achieved by using an exhaust system that directs the flow of gases. Apart from directing the flow of gases, the exhaust system also has the function of reducing the sound that is generated due to the pressure pulsations that occur during the combustion of gases in the engine. The flow of gases through the exhaust system leads to some back pressure due to phenomenon such as friction, contraction and expansion of exhaust gases and the turbulence of gases. Back pressure affects the engine performance as the gases in the exhaust system offer resistance to the gases that are trying to escape from the engine. Due to this resistance, the volumetric efficiency of the engine decreases, causing increased fuel consumption and loss of performance. Hence, it is very important to consider the back pressure of an exhaust system from the early stages of design. In the industry, it is not viable to make prototypes every time a small change is carried out to the design. Simulations are very useful for checking concepts and ensuring that the back pressure targets are met. The aim of the master thesis is to evaluate 1D and 3D CFD simulation methods for exhaust back pressure that are currently in use at Volvo Cars. This evaluation was carried out by comparing the results from the simulations to those obtained from physical tests. Once the methods were evaluated, they were then modified to replicate the tests better. Simulations with the modifications were then run, and the differences in results were observed. The modifications made an improvement for two out of the three geometries. It was found out that modelling small geometrical features inside the exhaust systems and calibrating the models with the right heat transfer coefficients contribute greatly to better the correlations between the results from the simulations and experimental tests. The work in this thesis can be used as a reference for future modelling, as it calls for improvements to the methods that are currently in place at Volvo Cars.
Keywords: Transport; Hållbar utveckling; Farkostteknik; Transport; Sustainable Development; Vehicle Engineering